Prevalence of open air defecation and awareness and practices of sanitary latrine usage in a rural village of Raipur district - Panda, Prem S.; Chandrakar, Aditi; Soni, Gopal P. (International Journal Of Community Medicine And Public Health, 2017)
Background: The practice of open defecation is rampant in India and our country is home to the world’s largest population of people who defecate in the open. Insanitary disposal of human excreta, along with unsafe drinking water and poor hygiene conditions, is a leading cause of morbidity and mortality in low-income countries. The study was conducted with objective to find sanitary latrine usage, prevalence of open air defecation and awareness related to diseases caused by open air defecation in the rural population of a village in Raipur district. Methods: A total of 155 households were selected for the study using simple random sampling technique by lottery method. One member from each household, preferably the head of the family (if not available, any elder person in the family), was interviewed personally. A structured questionnaire was used to collect information regarding the background characteristics, awareness and practices about sanitary latrine usage. Results: Majority of the study participants 109 (70.3%) had sanitary latrines in their houses. The prevalence of open air defecation in the study area was found to be 23.2%. Around 2/3rd (65.2%) of study subjects were not aware about spread of disease due to open air defecation. Conclusions: Awareness regarding spread of diseases due to open air defecation is poor. Effective political commitment and administrative support will be the key points of success of the Swachha Bharat Abhiyaan program.